The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.02.28.433246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic analysis of loss of Gli1 in neural stem cells responding to demyelination in the mouse brain

Abstract: In the adult mammalian brain, Gli1 expressing neural stem cells reside in the subventricular zone and their progeny are recruited to sites of demyelination in the white matter where they regenerate oligodendrocytes, the myelin forming cells. Remarkably, genetic loss or pharmacologic inhibition of Gli1 enhances the efficacy of remyelination by these neural stem cells. To understand the molecular mechanisms involved, we performed a transcriptomic analysis of this Gli1-pool of neural stem cells. We compared murin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Indeed, Gpnmb expression was significantly lower in Gli1 NULL vNSCs compared to Gli1 HET vNSCs following demyelination (Fig. 1A), although there was no difference in Gpnmb levels in the healthy brain (Samanta, 2021). This indicates that Gli1 is necessary for upregulation of Gpnmb following demyelination but not required for its baseline expression in healthy brains.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Indeed, Gpnmb expression was significantly lower in Gli1 NULL vNSCs compared to Gli1 HET vNSCs following demyelination (Fig. 1A), although there was no difference in Gpnmb levels in the healthy brain (Samanta, 2021). This indicates that Gli1 is necessary for upregulation of Gpnmb following demyelination but not required for its baseline expression in healthy brains.…”
Section: Discussionmentioning
confidence: 90%
“…Our previous studies have shown that loss of Gli1 in vNSCs of the adult SVZ, results in enhanced recruitment and regeneration of myelinating oligodendrocytes in response to demyelination of the white matter corpus callosum (CC) (Radecki et al, 2020;Samanta et al, 2015). To determine the molecular mechanisms involved, we compared the transcriptomes of vNSCs isolated from the healthy and demyelinated brains of the knock-in Gli1 CreER/Wt (Gli1 HET ) mice with one copy of Gli1, and Gli1 CreER/CreER (Gli1 NULL ) mice with loss of Gli1 expression (Samanta, 2021). We probed the top 100 differentially expressed genes in the Gli1 HET vs. Gli1 NULL vNSCs following demyelination, for genes shared amongst three or more GO terms related to cell survival, migration and differentiation.…”
Section: Identification Of Gpnmb As a Novel Inhibitor Of Oligodendrogenesis In Ventral Neural Stem Cellsmentioning
confidence: 99%
See 3 more Smart Citations